THE ROLE OF CONSERVATIVE DENTAL RECORDS IN SUPPORTING FORENSIC ODONTOLOGY IDENTIFICATION: A PUBLIC HEALTH PERSPECTIVE - Yessy Andriani Fauziah; Eveline Yulia Darmadi; Cindy Hendrawan; Dwi Setianingtyas (HEARTY, 2026)
Forensic odontology plays an important role in the identification of individuals, particularly in situations where other identification methods are no longer applicable. Conservative dentistry generates comprehensive clinical data, including restorations, radiographic images, and treatment history, which have the potential to support forensic identification processes. This study aims to analyze the role of conservative dental records in supporting forensic odontological identification from a public health perspective. The method used is a narrative review based on scientific literature published between 2020 and 2026 that is relevant to the topic. The results indicate that dental records serve as reliable and individualized antemortem data, contributing significantly to the accuracy of identification, especially in mass disaster scenarios. However, their utilization remains limited due to challenges such as lack of standardization, inconsistent documentation quality, and absence of integrated database systems. Advances in digital dentistry and artificial intelligence offer opportunities to improve the efficiency and accuracy of identification processes, although ethical and regulatory aspects must be carefully considered. In conclusion, strengthening the quality, standardization, and integration of dental records is essential to support effective forensic identification systems and public health frameworks.